Creative Strategies and Network Development of a Nonformal Music Education Institution in Indonesia: A Case Study of Purwa Caraka Music Studio - Lutfia Okta Riwayati; Tika Puspita Sari; Ayu Sarah Yanty Pasaribu; Khurotin Anggraeni; Abdulrasheed Olowoselu (Program Studi Pendidikan Musik FBS UNP, 2025)
Objective: This study aims to examine the creative strategies employed by Purwa Caraka Music Studio (PCMS) in developing its music education institution and to analyze the music education network that has been established and expanded across Indonesia. Method: This research uses a qualitative method with a case study approach, conducted through document analysis, observation, and interviews with PCMS instructors, students, and alumni. The data were analyzed using data reduction, data display, and inductive conclusion drawing techniques. Results and Discussion:The findings indicate that PCMS’s creative strategies are reflected in the implementation of fun learning, a flexible curriculum, diversification of musical genres, regular concert programs, and the use of digital media for online learning and promotion. In addition, PCMS has successfully developed a network of more than 78 branches across Indonesia, often referred to as the “octopus phenomenon,” which has expanded public access to non-formal music education. This network functions not only structurally but also as a social and cultural ecosystem, supported by alumni contributions in the entertainment, education, and creative industries. Conclusion: Thus, PCMS plays a significant role in supporting the development of musical creativity within Indonesian society. The institution serves not only as a place for music learning but also as a center for character development, creativity cultivation, and a cultural agent that strengthens the national music ecosystem.